Patriot Santri Caderisation in Improving Organisational Commitment at Islamic Boarding School - Jadwa An-Nazih; Hasan Baharun (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aims to determine the regeneration efforts of the Nurul Jadid Islamic Boarding School in increasing organizational commitment. The method used is a qualitative case study approach. This research was conducted at the santri patriot organization at the Nurul Jadid Islamic Boarding School Paiton Probolinggo. The efforts of the Nurul Jadid Islamic Boarding School to increase students' organizational commitment are the regeneration program; Character education, scholarships, training, and dedication in the form of direction that can motivate patriotic students to encourage the spirit of learning so that it is expected to increase the commitment of the patriot santri organization.